Necrotizing Fasciitis Resulting from Human Bites: A Report of Two Cases of Disease Caused by Group A Streptococci - Christopher A Sikora; Jack Spielman; Kerry MacDonald; Gregory J Tyrrell; John M Embil (Canadian Journal of Infectious Diseases and Medical Microbiology)
Necrotizing fasciitis is a serious and potentially life-threatening condition. Although bite wounds are common, they are not frequently reported as a cause of necrotizing fasciitis. In the present article, two cases of bite-associated necrotizing fasciitis caused by group A streptococcus are reported. Previously published cases are also reviewed.